Mcnylon and process for its production

CN117417634BActive Publication Date: 2026-10-23JIANGSU YIYUAN NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311343612.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2026-10-23
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

[0004]针对上述细菌纤维素改性MC尼龙强度不足的问题,本发明提供了一种MC尼龙及其制备方法,能够增强细菌纤维素改性MC尼龙的机械性能

Benefits of technology

1、本发明在细菌纤维素改性MC尼龙中加入了氧化石墨烯,其不仅具有石墨烯的强度,还具有多种含氧基团可以和细菌纤维素的羟基反应,使得二者结合更紧密,能够提高MC尼龙的机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses MC nylon and a preparation method thereof, which is prepared from raw materials including the following components in parts by mass: 100 parts of caprolactam, 0.4-6 parts of graphene oxide, 0.1-20 parts of a catalyst, 0.1-5 parts of bacterial cellulose, 0.005-0.5 parts of a light stabilizer and 0.1-17 parts of an activator; the graphene oxide is added in the bacterial cellulose modified MC nylon, the graphene oxide not only has the strength of graphene, but also has various oxygen-containing groups which can react with hydroxyl groups of the bacterial cellulose, so that the graphene oxide and the bacterial cellulose are combined more closely, and the mechanical properties of the MC nylon are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to nylon materials, and more specifically, to an MC nylon and its preparation method. Background Technology

[0002] Polycaprolactam, commonly known as nylon 6, is a linear polyamide produced by the ring-opening polymerization of caprolactam monomer. MC nylon, or monomer-cast nylon, is a type of nylon 6, typically produced by directly polymerizing caprolactam in a mold using an alkaline-catalyzed polymerization method and then solidifying it. Compared to other nylon materials, such as hydrolyzed nylon, nylon 6 has a lower polymerization temperature (around 160℃), a faster reaction rate, is easier to mold, and produces finished products with better mechanical properties.

[0003] To obtain MC nylon with better performance, existing MC nylon can be modified. Adding substances such as glass fibers, rubber, or stabilizers can improve the rigidity, strength, and toughness of MC nylon. Adding glass fibers is a common reinforcement method. Glass fibers arrange themselves in nylon to form a skeleton-like structure, which can transmit external pressure along the fiber skeleton axis, distributing stress throughout and improving the mechanical properties of nylon. However, glass fibers are harmful to the human body and can damage the skin, eyes, and respiratory system. Bacterial cellulose, as a biomaterial, has good biocompatibility and biodegradability, and like glass fibers, it can form a skeleton-like network structure. Using bacterial cellulose to replace glass fibers to reinforce MC nylon is a promising approach. Studies have shown that replacing part of the glass fibers with bacterial cellulose has a good effect on modifying and reinforcing MC nylon; however, using bacterial cellulose alone is not ideal because bacterial cellulose has a large number of hydroxyl groups, which bind a large amount of water, resulting in insufficient strength in the modified MC nylon. Summary of the Invention

[0004] To address the problem of insufficient strength in bacterial cellulose-modified MC nylon, this invention provides an MC nylon and its preparation method, which can enhance the mechanical properties of bacterial cellulose-modified MC nylon.

[0005] To achieve the above objectives, the present invention provides an MC nylon, which, by weight, is made from raw materials comprising the following components: 100 parts caprolactam, 0.4-6 parts graphene oxide, 0.1-5 parts catalyst, 0.1-5 parts bacterial cellulose, 0.005-0.5 parts light stabilizer, and 0.1-5 parts activator.

[0006] This invention employs a mixture of graphene oxide and bacterial cellulose for modification. The skeletal structure of bacterial cellulose enhances the dispersibility of graphene oxide, thereby improving the resistance of the MC nylon to external forces. Simultaneously, the various oxygen-containing groups in graphene oxide can react with the hydroxyl groups of bacterial cellulose, forming a tight bond and removing excess water, thus solving the problem of insufficient strength of bacterial cellulose itself. Furthermore, the addition of light stabilizers enhances the anti-aging properties of the MC nylon.

[0007] Preferably, the raw materials are in the following proportions by weight: 100 parts caprolactam, 1-5 parts graphene oxide, 1-3 parts catalyst, 0.2-4 parts bacterial cellulose, 0.01-0.4 parts light stabilizer, and 1-3 parts activator.

[0008] Preferably, the catalyst is selected from one or more of sodium, sodium hydroxide, and sodium methoxide.

[0009] Preferably, the light stabilizer is selected from HS-944 hindered amine light stabilizer and / or 4050H light stabilizer.

[0010] Preferably, the activator is selected from one or more of 2,4-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, and triphenylmethane triisocyanate.

[0011] Preferably, the bacterial cellulose is extracted from Acetic Acid Bacillus.

[0012] The beneficial effect of adopting this preferred method is that Acetic Acid Bacillus has a strong ability to produce bacterial cellulose.

[0013] Another aspect of the present invention provides a method for preparing the above-mentioned MC nylon, comprising the following steps: (1) Melt caprolactam to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 130~160℃ and perform vacuum dehydration for 25~30 min to obtain a dehydrated mixture. (3) After restoring normal pressure, add the catalyst and light stabilizer to the dehydrated mixture obtained in step (2), purge with nitrogen for protection and vacuum dehydrate for 10-25 min to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add the activator to the intermediate mixture obtained in step (3), and then pour it into a mold preheated to 160~185℃. After holding at 140~170℃ for 10~30 minutes, cast the hot-cast nylon. (5) After cooling the hot-cast nylon obtained in step (4) to room temperature, demold it and then treat it with water and oil to obtain the MC nylon.

[0014] The preparation method is simple, and the resulting MC nylon has high strength and is decomposable.

[0015] Through the above technical solution, the present invention achieves the following beneficial effects: 1. This invention incorporates graphene oxide into bacterial cellulose-modified MC nylon. Graphene oxide not only possesses the strength of graphene but also has various oxygen-containing groups that can react with the hydroxyl groups of bacterial cellulose, resulting in a tighter bond between the two and improving the mechanical properties of MC nylon.

[0016] 2. The bacterial cellulose used in this invention has a three-dimensional network structure, which can act as a skeleton in nylon. On the one hand, it can transmit stress, and on the other hand, the space it supports can improve the dispersibility of graphene oxide.

[0017] 3. This invention improves the anti-aging properties of MC nylon by adding light stabilizers. Detailed Implementation

[0018] The specific embodiments of the present invention will be described in detail below with reference to examples. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0019] In the following examples, the bacterial cellulose used was prepared in the following manner: A culture medium was prepared, comprising the following components: 50 g / L glucose, 4 g / L peptone, 5 g / L yeast extract, 5 g / L disodium hydrogen phosphate, and ultrapure water. The culture medium was sterilized at 120°C. Acetic acid bacteria were inoculated onto the culture medium and cultured at 25°C for 7 days. Bacterial cellulose was extracted.

[0020] Example 1: Weigh the following raw materials in parts by weight: 100 parts caprolactam, 0.4 parts graphene oxide, 0.1 parts sodium hydroxide, 0.1 parts bacterial cellulose, 0.005 parts HS-944 hindered amine light stabilizer, and 0.1 parts 2,4-diisocyanate.

[0021] Prepare MC nylon according to the following steps: (1) Melt caprolactam at 80℃ to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 130°C and perform vacuum dehydration for 25 min with a vacuum degree ≥ 0.1 MPa to obtain a dehydrated mixture. (3) After restoring normal pressure, sodium hydroxide and HS-944 hindered amine light stabilizer are added to the dehydrated mixture obtained in step (2), nitrogen gas is introduced for protection and vacuum dehydration is carried out for 10 min to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add 2,4-diisocyanate to the intermediate mixture obtained in step (2), and then quickly pour it into a mold preheated to 160°C. After holding at 140°C for 10 minutes, perform static casting to obtain hot-cast nylon. (5) After the hot-cast nylon obtained in step (4) is cooled to room temperature, it is demolded and then subjected to water treatment and oil treatment to obtain the MC nylon.

[0022] Example 2: Weigh the following raw materials in parts by weight: 100 parts caprolactam, 1 part graphene oxide, 0.5 parts sodium, 0.5 parts sodium methoxide, 0.2 parts bacterial cellulose, 0.01 parts 4050H light stabilizer, 0.5 parts hexamethylene diisocyanate, and 0.5 parts diphenylmethane diisocyanate.

[0023] Prepare MC nylon according to the following steps: (1) Melt caprolactam at 95℃ to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 140°C and perform vacuum dehydration for 30 min with a vacuum degree ≥ 0.1 MPa to obtain a dehydrated mixture. (3) After restoring normal pressure, sodium, sodium methoxide and HS-944 hindered amine light stabilizer are added to the dehydrated mixture obtained in step (2), nitrogen gas is introduced for protection and vacuum dehydration is carried out for 15 minutes to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add hexamethylene diisocyanate and diphenylmethane diisocyanate to the intermediate mixture obtained in step (2), and then quickly pour it into a mold preheated to 150°C. After holding at 165°C for 20 minutes, centrifuge casting is performed to obtain hot-cast nylon. (5) After the hot-cast nylon obtained in step (4) is cooled to room temperature, it is demolded and then subjected to water treatment and oil treatment to obtain the MC nylon.

[0024] Example 3: Weigh the following raw materials in parts by weight: 100 parts caprolactam, 5 parts graphene oxide, 3 parts sodium methoxide, 4 parts bacterial cellulose, 0.2 parts HS-944 hindered amine light stabilizer, 0.2 parts 4050H light stabilizer, and 3 parts triphenylmethane triisocyanate.

[0025] Prepare MC nylon according to the following steps: (1) Melt caprolactam at 110℃ to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 150°C and perform vacuum dehydration for 28 min with a vacuum degree ≥ 0.1 MPa to obtain a dehydrated mixture. (3) After restoring normal pressure, sodium methoxide and HS-944 hindered amine light stabilizer are added to the dehydrated mixture obtained in step (2), nitrogen gas is introduced for protection and vacuum dehydration is carried out for 20 min to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add triphenylmethane triisocyanate to the intermediate mixture obtained in step (2), and then quickly pour it into a mold preheated to 175°C. Keep it at 160°C for 25 minutes and perform static casting to obtain hot-cast nylon. (5) After the hot-cast nylon obtained in step (4) is cooled to room temperature, it is demolded and then subjected to water treatment and oil treatment to obtain the MC nylon.

[0026] Example 4: Weigh the following raw materials in parts by weight: 100 parts caprolactam, 5 parts graphene oxide, 5 parts sodium, 5 parts bacterial cellulose, 0.5 parts HS-944 hindered amine light stabilizer, and 5 parts 2,4-diisocyanate.

[0027] Prepare MC nylon according to the following steps: (1) Melt caprolactam at 110℃ to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 160°C and perform vacuum dehydration for 30 min with a vacuum degree ≥ 0.1 MPa to obtain a dehydrated mixture. (3) After restoring normal pressure, sodium methoxide and HS-944 hindered amine light stabilizer are added to the dehydrated mixture obtained in step (2), nitrogen gas is introduced for protection and vacuum dehydration is carried out for 25 minutes to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add triphenylmethane triisocyanate to the intermediate mixture obtained in step (2), and then quickly pour it into a mold preheated to 185°C. Keep it at 170°C for 30 minutes and perform static casting to obtain hot-cast nylon. (5) After the hot-cast nylon obtained in step (4) is cooled to room temperature, it is demolded and then subjected to water treatment and oil treatment to obtain the MC nylon.

[0028] Comparative Example 1: The other conditions are the same as in Example 1, except that the raw materials do not contain graphene oxide.

[0029] Comparative Example 2: The other conditions are the same as in Example 1, except that the raw materials do not contain bacterial cellulose.

[0030] Comparative Example 3: The other conditions are the same as in Example 1, except that the graphene oxide is replaced with graphene.

[0031] Comparative Example 4: Other conditions are the same as in Example 1, except that the raw materials do not contain HS-944 hindered amine light stabilizer.

[0032] Comparative Example 5: Other conditions are the same as in Example 1, except that the raw materials do not contain graphene oxide and HS-944 hindered amine light stabilizer.

[0033] Performance testing: The MC nylons prepared in the examples and comparative examples were subjected to performance tests using the following methods: Tensile strength was tested according to GB / T 1040-2006; The sample was placed in 85% solution and kept at 85℃ for 250 hours, then dried thoroughly. The tensile strength (aging) was then tested according to GB / T 1040-2006. Bending strength was tested according to GB / T 9341-2008; Test the ball indentation hardness according to GB / T 3398-2008; Impact strength was tested according to GB / T 1043-2008; The coefficient of friction was tested according to GB / T 3960-2016.

[0034] The results are shown in Table 1.

[0035] Table 1 Performance parameters of MC nylon obtained in the examples and comparative examples.

[0036] As shown in Table 1, the MC nylon prepared in the examples exhibits higher tensile strength, tensile strength (aging), flexural strength, ball indentation hardness, and impact strength compared to the MC nylon prepared in the comparative examples, and also has a lower coefficient of friction. This indicates that the MC nylon prepared in the examples possesses better mechanical properties and anti-aging properties. Comparing Examples 1, 1, and 3, it is shown that adding graphene oxide enhances the mechanical properties of MC nylon. However, because graphene is not oxidized, it cannot chemically bond with bacterial cellulose, and therefore its performance is inferior to the MC nylon prepared in Comparative Example 1. Comparing Examples 1, 1, and 2, the MC nylon without bacterial cellulose shows worse mechanical properties such as tensile strength and anti-aging properties, indicating that adding bacterial cellulose significantly improves these properties. Comparing Examples 1, 4, and 5, the tensile strength (aging) of the comparative examples without added light stabilizers is significantly lower than that of the examples, indicating that light stabilizers are essential for enhancing the anti-aging properties of MC nylon.

[0037] As can be seen from the above description, the present invention has the following advantages: it has better mechanical properties and anti-aging properties than ordinary MC nylon.

[0038] The preferred embodiments of the present invention have been described in detail above with reference to the examples. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0039] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0040] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. An MC nylon, characterized in that, The MC nylon is prepared by means of the following components, in parts by weight: 100 parts caprolactam, 0.4-6 parts graphene oxide, 0.1-5 parts catalyst, 0.1-5 parts bacterial cellulose, 0.005-0.5 parts light stabilizer, and 0.1-5 parts activator. The preparation method of MC nylon includes the following steps: (1) Melt caprolactam to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 130~160℃ and perform vacuum dehydration for 25~30 min to obtain a dehydrated mixture. (3) After restoring normal pressure, add the catalyst and light stabilizer to the dehydrated mixture obtained in step (2), purge with nitrogen for protection and vacuum dehydrate for 10-25 min to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add the activator to the intermediate mixture obtained in step (3), and then pour it into a mold preheated to 160~185℃. After holding at 140~170℃ for 10~30 minutes, cast the hot-cast nylon. (5) After cooling the hot-cast nylon obtained in step (4) to room temperature, demold it and then treat it with water and oil to obtain the MC nylon.

2. The MC nylon according to claim 1, characterized in that, The raw materials are in the following proportions by weight: 100 parts caprolactam, 1-5 parts graphene oxide, 1-3 parts catalyst, 0.2-4 parts bacterial cellulose, 0.01-0.4 parts light stabilizer, and 1-3 parts activator.

3. The MC nylon according to claim 1, characterized in that, The catalyst is selected from one or more of sodium, sodium hydroxide, and sodium methoxide.

4. The MC nylon according to claim 1, characterized in that, The light stabilizer is selected from HS-944 hindered amine light stabilizer and / or 4050H light stabilizer.

5. The MC nylon according to claim 1, characterized in that, The activator is selected from one or more of diisocyanate, diphenylmethane diisocyanate, and triphenylmethane triisocyanate.

6. The MC nylon according to claim 1, characterized in that, The bacterial cellulose was extracted from Acetic Acid Bacillus.

7. The method for preparing MC nylon according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Melt caprolactam to a molten state to obtain molten caprolactam; (2) Add graphene oxide and bacterial cellulose to the molten caprolactam obtained in step (1) and mix. Heat to 130~160℃ and perform vacuum dehydration for 25~30 min to obtain a dehydrated mixture. (3) After restoring normal pressure, add the catalyst and light stabilizer to the dehydrated mixture obtained in step (2), purge with nitrogen for protection and vacuum dehydrate for 10-25 min to obtain an intermediate mixture; (4) After the vacuum is released, stop the nitrogen gas supply, add the activator to the intermediate mixture obtained in step (3), and then pour it into a mold preheated to 160~185℃. After holding at 140~170℃ for 10~30 minutes, cast the hot-cast nylon. (5) After cooling the hot-cast nylon obtained in step (4) to room temperature, demold it and then treat it with water and oil to obtain the MC nylon.

Citation Information

Patent Citations

  • Nanocellulose enhanced and toughened MC nylon composite and preparation method thereof

    CN107353402A

  • Preparation method and application of bacterial cellulose enhanced graphene oxide paper

    CN113652885A